Impact of Conventional Cardiovascular Risk Factors on Left Internal Mammary Artery Graft Disease - Zuo, Hui-Juan; Nan, Nan; Yang, Hong-Xia; Wang, Jin-Wen; Song, Xian-Tao (Frontiers in Cardiovascular Medicine, 2022)
Background: The development of atherosclerosis was considered as the common cause of the stenosis of coronary artery grafts. Left internal mammary artery (LIMA) was the best artery graft for further effectiveness of coronary artery bypass grafting (CABG). We sought to assess the impact of known conventional cardiovascular risk factors (RFs) on LIMA graft stenosis. Methods: A retrospective study including 618 participants, who had recurrence of chest pain after CABG, aged ≥18 years, hospitalized for coronary angiography in Beijing Anzhen hospital between 2010 and 2017 was performed. All the participants were confirmed to have LIMA graft. Multivariate analysis was conducted to determine the relationship between conventional RFs and LIMA graft stenosis. Results: Of the study, 220 (35.6%) participants continued to smoke, 504 (81.6%) were overweight or obese, and 411 (66.5%) and 242 (39.2%) reported concomitant hypertension and diabetes, respectively. LIMA graft stenosis occurred in 161 participants (26.1%). Postoperative smoking, a CABG duration of ≥10 years and hyperglycemia without diabetes had an increased risk of LIMA graft stenosis, the odds ratio (OR) was 1.86 [95% confidence interval (CI): 1.26–2.78], 2.24 (95%CI:1.33–3.478), and 2.44(95% CI:1.39–4.32), respectively. Statin use (OR, 0.28; 95% CI: 0.25–0.5) and low-density lipoprotein cholesterol (LDL-C) < 1.8 mmol/L (OR, 0.27; 95% CI: 0.14–0.53) had a significantly decreased risk of LIMA graft stenosis. While, only 15.4% (95/618) achieved the target LDL-C level. Conclusions: Postoperative smoking and hyperglycemia without diabetes had an increased risk of LIMA graft stenosis. Statin use and LDL-C <1.8 mmol/L decreased the risk.